Poetiche del nonsense: l'esempio del Jabberwocky - Chiara Lepri (Firenze University Press, 2017)
This paper deepens the nonsense poetry theme with a specific reference to Jab-berwocky's poem, in Lewis Carroll's Through the Looking Glass (1871) and the creative use of portmanteau-words. It emerges that nonsense poetry is not just a reverie, but one of the many profiles with which children's literature is still ex-pressing today with significant results on the ludic and aesthetic level. This con-cerns the pedagogical investigation as it is an effective opportunity to redefine the experience from the unusual, from the possible and - utopically - from the impossible.